Quantum tomography of photon states encoded in polarization and picosecond time bins - Pilnyak, Y.; Zilber, P.; Cohen, L.; Eisenberg, H. S. (Phys. Rev. A, 2019)
A single photon has many physical degrees of freedom (DOF) that can carry the state of a high-dimensional quantum system. Nevertheless, only a single DOF is usually used in any specific demonstration. Furthermore, when more DOF are being used, they are analyzed and measured one at a time. We introduce a two-qubit information system, realized by two degrees of freedom of a single photon: polarization and time. The photon arrival time is divided into two time bins representing a qubit, while its polarization state represents a second qubit. The time difference between the two time bins is created without an interferometer at the picosecond scale, which is much smaller than the detector's response time. The two physically different DOF are analyzed simultaneously by photon bunching between the analyzed photon and an ancilla photon. Full two-qubit states encoded in single photons were reconstructed using quantum state tomography, both when the two DOF were entangled and when they were not, with fidelities higher than 96%.
Publisher: American Physical Society